Common and distinct neural connectivity in attention‐deficit/hyperactivity disorder and alcohol use disorder studied using resting‐state functional magnetic resonance imaging. (2nd April 2021) - Farré‐Colomés, Àlvar; Gerhardt, Sarah; Luderer, Mathias; Sobanski, Esther; Kiefer, Falk; Vollstädt‐Klein, Sabine
Abstract: Background: A link between attention‐deficit/hyperactivity disorder (ADHD) and alcohol use disorder (AUD) has been widely demonstrated. In this study, we used neuroimaging to investigate the connectivity traits that may contribute to the comorbidity of these disorders. Methods: The study included an AUD group ( N  = 18), an ADHD group ( N  = 17), a group with AUD + ADHD comorbidity ( N  = 12) and a control group ( N  = 18). We used resting‐state functional connectivity in a seed‐based approach in the default mode networks, the dorsal attention network, and the salience network. Results: Within the default mode networks, all affected groups shared greater connectivity toward the temporal gyrus when compared to the control group. Regarding the dorsal attention network, the Brodmann area 6 presented greater connectivity for each affected group in comparison with the control group, displaying the strongest aberrations in the AUD + ADHD group. In the salience network, the prefrontal cortex showed decreased connectivity in each affected group compared to the control group. Conclusions: Despite the small and unequal sample sizes, our findings show evidence of common neurobiological alterations in AUD and ADHD, supporting the hypothesis that ADHD could be a risk factor for the development of AUD. The results highlight the importance of an early ADHD diagnosis and treatment to reduce the risk of a subsequent AUD. Abstract : Using a neuroimaging approach, we examined resting‐state alterations in individuals with alcohol use disorder (AUD), attention deficit/‐hyperactivity disorder (ADHD), or both diagnoses combined, compared to individuals without any mental disorder regarding the connectivity of and between the dorsal attention, salience, and default mode networks. Specifically, dysregulations of motor regions worsen in the presence of both diagnoses. These results highlight the importance of an early ADHD diagnosis and treatment to reduce the risk for a subsequent AUD.